Chapter 3 Reforms of asylum seekers' reception during the 2010s Driving factors and multilevel governance arrangements - ponzo, irene (Taylor & Francis, 2022)
"This book provides a comparative overview of asylum seekers' reception throughout Europe by adopting a theoretical framework based on an analytical approach to the notion of multilevel governance. It challenges the tendency of the multilevel governance literature to overlook political controversies and conflicts and questions the assumption that it represents the best policymaking arrangement for promoting policy convergence. In doing so, it explores the functioning of the reception component of the Common European Asylum System in centralised states and federal/regional states and analyses its implementation at both national and local levels. The book reveals the heterogeneous development of reception policies not only across Member States but also within each country where solutions adopted at the local level generally diverge substantially. Furthermore, the overall centralization of policymaking on reception regardless the institutional structure, seems to leave little room for MLG arrangements tailored to specific localities and triggers tensions between central governments and local authorities. This book will be of key interest to scholars and students of migration and asylum studies, immigration, (multilevel) global governance and more broadly to comparative politics, European studies/politics, and public policy."